Effect of productive age on the real estate market - Tomáš Poláček; Jiří Oulehla; Jiří Luňáček (Trends Economics and Management, 2020)
Purpose of the article: With the ever-increasing development of property prices and the disproportionate number of new housing developments, the question is which factors have an impact on this phenomenon from the-out-of-the-box perspective. For the article, the main variables which influence the real estate market were selected by secondary research. These variables were chosen as independent variables. The dependent variable was explicitly created for this research as the Index of the Productive Age (IPA). Methodology/methods: Using statistical and econometric tools allowed us to determine which variables have a statistically significant effect on the development of prices and the whole nature of the real estate market. Scientific aim: The study deals with the effect of the size of the productive population on the real estate market, more precisely on the price of real estate. Findings: Finding that the "fuzzy" variable of age can have a significant influence on the real estate market. As a result, it can be stated that the larger the population of the productive age, the more real estate is being built, but also its prices increase. Conclusions: The sensitivity of IPA changes to selected variables. Also, within rising prices on the real estate market, it is possible to observe an increase in demand for alternative housing. Based on the research, the hypotheses were addressed in the discussion and conclusion.
Keywords: E43; R15; R31; 650; real estate; productive age; housing development; mortality